How the resilient ecophysiology of the sea lamprey allowed them to invade the Laurentian Great Lakes and could protect them from climate change - Wilkie, Michael P. (Frontiers in Fish Science, 2025)
Native to the Atlantic Ocean, anadromous sea lamprey (Petromyzon marinus) likely invaded the Laurentian Great Lakes in the mid 1800's-early 1900's following construction of the Erie Canal. Initially restricted to Lake Ontario, and some smaller nearby lakes, they entered Lake Erie via the Welland Canal in the early 1900s. Sea lamprey quickly became established in Lake Erie (1921), from which they invaded the three upper Great Lakes. Along with overharvest, predation (parasitism) by blood-feeding sea lamprey devastated commercial, sport and Indigenous fisheries including lake trout (Salvelinus namaycush) and whitefish and ciscoes (Coregonus sp.) populations. To deal with the crisis, the Great Lakes Fishery Commission (GLFC) was founded in 1955 with a mandate to eradicate sea lamprey. Sea lamprey were not eradicated, but a comprehensive sea lamprey control (SLC) program brought populations under control using barriers (dams) and traps to prevent spawning by adult lampreys, and chemical control using lampricides that selectively targeted larval sea lamprey in nursery streams draining into the lakes. In this synthesis the sea lamprey invasion is explored through the lens of “invasion theory” to characterize the likely vectors that introduced sea lamprey into the Great Lakes ecosystem, and to establish what eco-physiological features of sea lamprey led to their establishment and spread. The weight of evidence suggests that pre-existing adaptations and a robust physiology facilitated the sea lamprey's invasion of the Great Lakes. Key features likely included: (i) facultative anadromy, which allowed them to complete their entire life cycle in fresh water, (ii) a generalist diet enabling them to feed on a wide variety of fishes, (iii) the high fecundity of females that expedited their spread, (iv) a resilient thermal physiology, and (v) the availability of similar, suitable spawning and nursery habitat to that found in their native ranges. Many of these features may make sea lamprey relatively resilient to climate change, with changes in water temperature, water quality and hydrology having both negative and positive effects on the distribution of invasive populations in the Great Lakes, and imperiled populations native to the Western and Eastern Atlantic Ocean, and the Mediterranean Sea.